Application of integrated medical information management system in the risk assessment and prevention of perioperative venous thromboembolism in gynecological patients (医护一体化信息管理系统在妇科围手术期患者静脉血栓栓塞症风险评估及预防中的应用) - JIANG Zhihui (蒋志会); RONG Mingmei (戎明梅) (中西医结合护理)
Objective To improve the risk assessment and prevention of perioperative venous thromboembolism (VTE) in gynecological patients by using integrated information management system of medical care. Methods A quality management team was established to design the key issues of VTE prevention and formulate a standard procedure of evaluating, alarming and processing. The early warning risk management, evaluated by the structure-process-result system, was established to continuously improve the quality of preventive monitoring and management of VTE. Totally 407 patients with hospital admission between Jan and June 2019 were included as the control group, and another 343 patients with hospital admission between July and December 2019 were recruited as the observation group. The incidence of VTE was compared between two groups. Results The preliminary screening rate in the observation group was 100. 00%(343/343), which was significant higher than 74. 94%(305/407)in the control group (P＜0. 01). The implementation rates of preventive measures for low-risk patients and moderate-to high risk patients were increased significantly after using integrated information management system (P＜0. 01). There were 2(0. 58%) cases of VTE in low-risk patients in the observation group. There were 5(1. 23%) cases of VTE in low-risk patients and 7(1. 72%) cases in moderate-to-high risk patients in the control group. Conclusion The integrated medical care management system can optimize the medical communication channels, promote the standardization and homogenization of the prevention and control system of VTE for gynecological patients during the perioperative period, which can ensure the safety of patients and improve the medical quality. (目的 依托医护一体化信息管理系统, 改善妇科围术期患者静脉血栓栓塞症(VTE)风险评估及预防措施落实。方法 建立科室医护一体化VTE质量管理小组, 设计重点环节节点控制, 形成VTE评估-提醒-处置标准化预防流程, 完善预警风险管理, 以结构-过程-结果为评价体系, 对科室VTE预防监测管理和持续质量改进。以医护一体化信息管理系统在病区实施时间为节点, 将2019年1月—6月住院的407例患者设为对照组, 2019年7月—12月343例患者设为观察组。对比两组VTE发生率。结果 观察组住院患者VTE风险评估初筛率为100. 00%(343/343), 相较于对照组的74. 94%(305/407)上升, 差异有统计学意义(P＜0. 01)。实施医护一体化信息管理后, VTE低危、中危及以上患者预防措施落实率均较实施前提升(P＜0. 01)。观察组中危及以上患者VTE发生2(0. 58%)例; 对照组低危患者VTE发生5(1. 23%)例, 中危及以上患者VTE发生7(1. 72%)例。结论 医护一体化管理系统能够优化医护沟通渠道, 促进妇科围术期患者VTE防控体系标准化和同质化, 保障患者安全, 提升医疗质量。)